University Students' Awareness and Preparedness for Natural Disasters: A Study on Preventing Landslides, Earthquakes, and Volcanic Eruptions in Indonesia - Yoshinori, Fujikawa; Tuswadi, Tuswadi; Takehiro, Hayashi; Tetsuo, Isozaki; Subekti, Niken (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study seeks to understand the disaster-prevention consciousness focused on landslide, earthquake, and volcanic eruption among 22 students pursuing a major in Geography in the Social Science Faculty, Semarang State University (UNNES), Indonesia. It analyzed the students’ consciousness through short comments toward questions “What can we do?”, which focused on preventing, defending, reducing, and mitigating the impacts of the three kinds of natural disasters. The average number of the description was 5.7, and the median was 5. More than half of the students mentioned points related to “before disaster and usual life,” “after disaster and restoration,” “hardware/structural,” and “software/non-structural.” All the answers described ideas with reasons. But only four students described ideas based on educational viewpoints, indicating students’ lack of scientific viewpoints in elaborating their ideas about disaster prevention. This finding calls for improving students’ consciousness regarding disaster prevention through education.AbstrakPenelitian ini bertujuan untuk memahami kesadaran pencegahan bencana yang difokuskan pada tanah longsor, gempa bumi, dan letusan gunung berapi di antara 22 mahasiswa yang mengambil jurusan Geografi di Fakultas Ilmu Sosial, Universitas Negeri Semarang (UNNES), Indonesia. Kesadaran mahasiswa dianalisis melalui komentar singkat terhadap pertanyaan "Apa yang bisa kita lakukan?", yang difokuskan pada pencegahan, pertahanan, pengurangan, dan mitigasi dampak dari tiga jenis bencana alam tersebut. Rata-rata jumlah deskripsi adalah 5,7, dan median adalah 5. Lebih dari setengah mahasiswa menyebutkan poin-poin yang terkait dengan "sebelum bencana dan kehidupan biasa," "setelah bencana dan pemulihan," "perangkat keras/struktural," dan "perangkat lunak/non-struktural." Semua jawaban menggambarkan ide-ide dengan alasan yang mendasarinya. Namun, hanya empat mahasiswa yang menguraikan ide-ide berdasarkan sudut pandang pendidikan, yang menunjukkan kurangnya sudut pandang ilmiah dalam mengelaborasi ide-ide mereka tentang pencegahan bencana. Temuan ini menunjukkan perlunya peningkatan kesadaran mahasiswa mengenai pencegahan bencana melalui pendidikan.  How to Cite: Yoshinori, F, Tuswadi, Takehiro, H, Tetsuo, I., Subekti, N. (2024). "University Students' Awareness and Preparedness for Natural Disasters: A Study on Preventing Landslides, Earthquakes, and Volcanic Eruptions in Indonesia. TARBIYA: Journal of Education in Muslim Society, 11(1), 81-92. doi:10.15408/tjems.v11i1.40444.